1994
DOI: 10.1021/jo00081a031
|View full text |Cite
|
Sign up to set email alerts
|

Ring opening and closure and oxygen isotope exchange of cyclic sulfinate esters

Abstract: Alkaline ring opening and the reverse ring closure in an aqueous acid solution of cyclic sulfinate esters (sultines), 3H-2,l-benzoxathiole 1-oxide (la) and 3,4-dihydro-2,l-benzoxathiin 1-oxide (lb), have kinetically been studied at 25 O C . The sultine la is more reactive than l b in both the opening and closure reactions. However, acid-catalyzed oxygen isotope exchange of the 180-labeled sultine la was found to be slower than that of the labeled lb. The contrasting reactivities of the five-and sixmembered sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Carbamates are characterized by the lone pair of electrons on N, which can delocalize into the π*orbital of the carbonyl group by an ηN → π* C=O interaction (similar to that reported for ηN → π* C=S interaction). 15 This facilitates the formation of a tetrahedral structure, which can be a transition state in the concerted mechanism or an intermediate in the stepwise one.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Carbamates are characterized by the lone pair of electrons on N, which can delocalize into the π*orbital of the carbonyl group by an ηN → π* C=O interaction (similar to that reported for ηN → π* C=S interaction). 15 This facilitates the formation of a tetrahedral structure, which can be a transition state in the concerted mechanism or an intermediate in the stepwise one.…”
Section: Introductionmentioning
confidence: 91%
“…22 The aminolysis of heterocycle carbamates 7-12 can proceed by the three mechanisms discussed above (Scheme 1), depending on the basicity of the amine, the nature of the leaving group, the solvent used, and the classification of the N atom of the nonleaving group. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The mechanism based on the formation of the isocyanate was ruled out because carbamates 7-12 do not have hydrogen atoms, which are required for the elimination. The BAC 2 mechanism can proceed by a concerted mechanism (Scheme 1, pathway b) or stepwise mechanism in which the ratedetermining step is the formation of a tetrahedral intermediate or amine catalysis or the expulsion of the leaving group (Scheme 1, pathway a) in the rate-determining step.…”
Section: Amine = Morph or Pipmentioning
confidence: 99%
“…It was found that a cyclic sulfinate ester (sultine) undergoes ring opening in an aqueous alkaline solution to give [ 18 O]‐sulfinate ion, after alkaline hydrolysis with H 2 18 O, while the cyclic sulfinate is stable in an acidic aqueous solution. Alkaline ring opening and the reverse ring closure in an aqueous acid solution of cyclic sulfinate esters have been studied extensively . Hydrolysis of a sulfinate ester is formally similar to that of a carboxylate ester (Scheme a).…”
Section: Synthetic Challengesmentioning
confidence: 99%
“…1-2 For example, the acid hydrolysis of alkyl sulfinate esters as well as cyclic sulfinates proceeds in a concerted SN2 type mechanism, [3][4] while the base catalyzed hydrolysis of cyclic sulfinates with a phenolic leaving group takes place through a hypervalent intermediate. 5 However, there is little report on the aminolysis of sulfinate esters.…”
mentioning
confidence: 99%